2018
DOI: 10.1002/2017jd027796
|View full text |Cite
|
Sign up to set email alerts
|

Foehn Event Triggered by an Atmospheric River Underlies Record‐Setting Temperature Along Continental Antarctica

Abstract: A record‐setting temperature of 17.5°C occurred on 24 March 2015 at the Esperanza station located near the northern tip of the Antarctic Peninsula (AP). We studied the event using surface station data, satellite imagery, reanalysis data, and numerical simulations. The Moderate Resolution Imaging Spectroradiometer Antarctic Ice Shelf Image Archive provides clear evidence for disintegration and advection of sea ice, as well as the formation of melt ponds on the ice sheet surface at the base of the AP mountain ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(159 citation statements)
references
References 64 publications
3
138
0
Order By: Relevance
“…The sea level pressure field showed that a deep low‐pressure system was blocked from moving eastward and thus stagnated near Prydz Bay. These synoptic conditions were favorable for the large‐scale meridional inland advection of warm, moist air masses (Bozkurt et al, ). The blocking situation and northerly wind at the front of the cyclone fed the low‐level poleward flow of heat and moisture to Panda‐1 AWS, resulting in peak water vapor pressure and temperature on 4 July.…”
Section: Meteorological Conditions At Panda Station In 2011mentioning
confidence: 99%
See 1 more Smart Citation
“…The sea level pressure field showed that a deep low‐pressure system was blocked from moving eastward and thus stagnated near Prydz Bay. These synoptic conditions were favorable for the large‐scale meridional inland advection of warm, moist air masses (Bozkurt et al, ). The blocking situation and northerly wind at the front of the cyclone fed the low‐level poleward flow of heat and moisture to Panda‐1 AWS, resulting in peak water vapor pressure and temperature on 4 July.…”
Section: Meteorological Conditions At Panda Station In 2011mentioning
confidence: 99%
“…Synoptic weather systems have the potential to strongly impact the surface energy flux through longwave radiation and mixing (Gallée & Gorodetskaya, 2010;Brauna et al, 2001;Xie et al, 2002;Genthon et al, 2013;Bozkurt et al, 2018;Vignon et al, 2018). Bozkurt et al (2018) studied a record-setting temperature event occurred at the northern tip of the Antarctica Peninsula (AP), caused by an atmospheric river that triggered a widespread foehn event. Cloud formation at the windward side provides the upper atmosphere with heat via water vapor condensation, also increasing the temperature at the leeward (foehn) side.…”
Section: Journal Of Geophysical Research: Atmospheresmentioning
confidence: 99%
“…Almost simultaneously, Esperanza station (6324 ′ S, 5659 ′ W, 13 m) located at the tip of the Antarctic Peninsula registered the highest temperatures ever recorded for continental Antarctica (Skansi et al, 2017) (17.5 • C on 24 March 2015, see Figure S1b). This extreme Antarctic heat wave triggered a significant melting on the Larsen C ice sheet (Munneke et al, 2018) and was ultimately traced to foehn-induced warming that resulted from a landfalling atmospheric river (Bozkurt et al, 2018). Floods and extreme precipitation were also reported during the second half of March 2015 along the semiarid coast of Northern Peru and Ecuador (Bendix et al, 2017) Given the rarity of these events, the extreme nature of these environments and the fact that they occurred simultaneously over a large region of the Eastern Pacific, we look for a common large-scale origin of this compound extreme event.…”
Section: Introductionmentioning
confidence: 99%
“…For Davies Dome, very high mean daily air temperature anomalies were connected to a pattern with low‐pressure areas on both sides of the AP, during which air mass was advected from the west and crossed over the AP. It is, therefore, more likely that in this case adiabatic warming of descending air and foehn winds (Bozkurt et al ., ) were the driving mechanisms of the air temperature increase at Davies Dome. Most of the higher elevated sites in the AP region are covered by mountain glaciers and ice caps, and their mass balance is, therefore, susceptible to surface energy balance changes, influenced by air mass advection (e.g., Braun et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, as the trajectories traversed and then descended the higher‐elevated region of the AP, adiabatic warming and drawdown of potentially warmer air from above (Kuipers Munneke et al ., ) might explain the warm temperature anomalies. Occasionally, a combination of a foehn situation (e.g., Cape et al ., ) and a warm air advection (Bozkurt et al ., ) can lead to extreme air temperatures over 17°C, as occurred on DD site on March 23, 2015 (World Meteorological Organization, ) during synoptic pattern [3, 2].…”
Section: Driving Mechanisms Of Atmospheric Circulation–air Temperaturmentioning
confidence: 97%